Mutations in BICD2 Cause Dominant Congenital Spinal Muscular Atrophy and Hereditary Spastic Paraplegia - Oates, Emily C.; Rossor, Alexander M.; Hafezparast, Majid; Gonzalez, Michael; Speziani, Fiorella; MacArthur, Daniel G.; Lek, Monkol; Cottenie, Ellen; Scoto, Mariacristina; Foley, A. Reghan; Hurles, Matthew; Houlden, Henry; et al. (American journal of human genetics, 2013)
Dominant congenital spinal muscular atrophy (DCSMA) is a disorder of developing anterior horn cells and shows lower-limb predominance and clinical overlap with hereditary spastic paraplegia (HSP), a lower-limb-predominant disorder of corticospinal motor neurons. We have identified four mutations in bicaudal D homolog 2 (Drosophila) (BICD2) in six kindreds affected by DCSMA, DCSMA with upper motor neuron features, or HSP. BICD2 encodes BICD2, a key adaptor protein that interacts with the dynein-dynactin motor complex, which facilitates trafficking of cellular cargos that are critical to motor neuron development and maintenance. We demonstrate that mutations resulting in amino acid substitutions in two binding regions of BICD2 increase its binding affinity for the cytoplasmic dynein-dynactin complex, which might result in the perturbation of BICD2-dynein-dynactin-mediated trafficking, and impair neurite outgrowth. These findings provide insight into the mechanism underlying both the static and the slowly progressive clinical features and the motor neuron pathology that characterize BICD2-associated diseases, and underscore the importance of the dynein-dynactin transport pathway in the development and survival of both lower and upper motor neurons.